Frozen Section Library: Gynecologic Pathology Intraoperative Consultation - Coffey, Donna M.; Ramzy, Ibrahim (Frozen Section Library, 2012)
Frozen sections are performed while a patient is undergoing surgery as a basis for making an immediate diagnosis that will impact treatment decisions. Frozen section diagnosis is often a highly demanding situation for the pathologist who must render a diagnosis quickly, based on careful gross examination of specimens to select optimal areas for microscopic examination. The Frozen Section Library series will provide concise, user-friendly, site specific handbooks that are well illustrated and highlight the pitfalls, artifacts and differential diagnosis issues that arise in the hurried frozen section scenario. Donna M. Coffey, M.D., is Assistant Professor, Department of Pathology and Laboratory Medicine, The Methodist Hospital, Houston, Texas and Weill Medical College of Cornell University, New York, New York. Ibrahim Ramzy, M.D., is Professor of Pathology - Laboratory Medicine & Obstetrics-Gynecology, University of California, Irvine, California and Adjunct Professor of Pathology, Baylor College of Medicine, Houston, Texas.